NATA DE COCO PROCESSING TECHNOLOGY AT PT. TROPICA NUCIFERA INDUSTRY YOGYAKARTA - Modjo, Ardiyanto Saleh; Balu, Miranti; Bait, Yoyanda; Rachman, Agus Bahar; Saman, Widya Rahmawaty; Antuli, Zainudin (Universitas Negeri Gorontalo, 2025)
This study aims to investigate the Nata de Coco Processing Technology at PT. Tropica Nucifera Industry in Bantul Regency, DIY Province, Yogyakarta. The focus of this activity is on understanding and exploring the Nata de Coco production process carried out by the company. The method employed for data collection in this study involves field observations with active participation in each stage of Nata de Coco processing and conducting interviews with employees. The objective of this method is to obtain a comprehensive overview of the Nata de Coco processing techniques at PT. Tropica Nucifera Industry in Bantul Regency, DIY Province, Yogyakarta. Based on the research findings, it can be concluded that the Nata de Coco processing process at PT. Tropica Nucifera Industry consists of eight stages. These stages include container preparation, media production, starter production, pouring the media into containers, seedling, harvesting, cutting, and washing.